ANALYSIS OF THE INCIDENT OF ARI IN TODDLER CHILDREN 0-59 MONTHS - Marisa, Oci; Lilis Suryani; Arie Wahyudi (LPPM STIKES Al-Ma'arif Baturaja, 2024)
ISPA is a disease that is often referred to as one of the top 10 diseases in developing countries and ISPA is the number one disease in the top ten list of diseases that is a trend in patient visits to health centers. ISPA cases in Community Health Centers have fluctuated over the last three years, and there has been no research regarding ISPA cases in children aged 0-59 months in Community Health Centers. The design of this research is quantitative with a cross-sectional approach. The population of this study were parents of children under five who were seeking treatment at the Community Health Center in 2024. The sample in this study was 78 people. The sampling method uses purposive sampling. This research was carried out on February 15-March 14 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test. The results of the study showed that there was a relationship between exclusive breastfeeding (p value 0.000) and the use of mosquito coils (p value 0.000). There is no relationship between age (p value 1.000), gender (p value 0.37) and smoking habits at home (p value 0.20) on the incidence of ARI in children under five 0-59 months at the Rawa Bening Community Health Center in 2024. The conclusion is there exclusive breastfeeding and the use of mosquito coils. There is no relationship between age, gender and smoking habits at home. For the Community Health Center, the Community Health Center should provide health education about exclusive breastfeeding both at the Community Health Center and at the Posyandu as well as how to prevent ISPA in the home environment.